IMPLIKASI YURIDIS KEKABURAN MAKNA KEPENTINGAN UMUM DALAM UNDANG-UNDANG PENGADAAN TANAH BAGI PEMBANGUNAN UNTUK KEPENTINGAN UMUM - Muwaid Muwaid (Al Hikmah: Jurnal Studi Keislaman, 2015)
Research on the juridical implications of the vague meaning of public interest is a normative legal one aimed at answering the problem of the meaning of public interest in the legislation, and the implications of vague meaning of public interest in the land acquisition legislation.The results showed that the concept of public interest in the law No. 2 of 2012 vaguely formulated as a result of the vague meaning of public interest in the legislation resulted in the lack of legal certainty in its implementation, an activity that is initially for the public interest, but in its development it could be for the business interest and profit-oriented goals.